Synergistic N‐Heterocyclic Carbene/Palladium‐Catalyzed Umpolung 1, 4‐Addition of Aryl Iodides to Enals. (26th November 2019) - Yang, Wenjun; Ling, Bo; Hu, Bowen; Yin, Haolin; Mao, Jianyou; Walsh, Patrick J.
Abstract: An umpolung 1, 4‐addition of aryl iodides to enals promoted by cooperative (terpy)Pd/NHC catalysis was developed that generates various bioactive β, β‐diaryl propanoate derivatives. This system is not only the first reported palladium‐catalyzed arylation of NHC‐bound homoenolates but also expands the scope of NHC‐induced umpolung transformations. A diverse array of functional groups such as esters, nitriles, alcohols, and heterocycles are tolerated under the mild conditions. This method also circumvents the use of moisture‐sensitive organometallic reagents. Abstract : Nimm zwei : Synergistische Katalyse zwischen NHC‐ und Pd‐Katalysatoren ermöglicht die konjugierte Addition von Aryliodiden an Enale unter redox‐neutralen Bedingungen. Diese Methode umgeht die Verwendung feuchtigkeitsempfindlicher metallorganischer Reagentien und ist verträglich mit zahlreichen Funktionen wie Estern, Nitrilen, Alkoholen und Heterocyclen.